Technology Enhanced Learning (TEL) of Finite State Machines (FSMs) - Han, Qin Qian (2019)
The advent of technology has enabled Technology Enchanced Learning (TEL) to be integrated in the education system. To expand the TEL field, a platform-independent Java application that generates all possible configurations of Finite State Machines (FSMs) was developed. The purpose of the application is to provide a virtual learning platform that allows users to practice the analysis of FSMs continuously. The final application was proved to be functional and had served its main purpose. This report highlights the fundamental concepts of FSM, including sequential circuits, state transition table and state diagram. A major section of the report describes the development strategies and methods used to configure a FSM and build the application. The report concludes with a discussion on further improvements that could be made.